Unprecedented enhancement of piezoelectricity of wurtzite nitride semiconductors via thermal annealing - Shubham Mondal; Md Mehedi Hasan Tanim; Garrett Baucom; Shaurya S. Dabas; Jinghan Gao; Jiangnan Liu; Zhengwei Ye; Venkateswarlu Gaddam; Aiden Ross; Long-Qing Chen; Honggyu Kim; Roozbeh Tabrizian; et al. (Nature Communications)
Abstract Incorporating rare-earth elements into wurtzite nitride semiconductors, such as scandium-alloyed aluminum nitride (ScAlN), significantly enhances the piezoelectric response, which is vital for a broad range of acoustic, electronic, photonic, and quantum applications. To date, however, the measured piezoelectric response of nitride semiconductors is far below what theory has predicted. Herein, we demonstrate a simple, scalable, post-growth thermal annealing process that can dramatically boost the piezoelectric response of ScAlN. We achieve a 3.5-fold increase in the piezoelectric modulus, d33 for ScAlN, from 12.3 pC/N in the as-grown state to 45.5 pC/N, which is eight times larger than that of AlN commercially used in 5 G cellphones. The observed enhancement is unambiguously confirmed by three separate measurement techniques. Detailed material characterization techniques reveal that optimized annealing conditions significantly improve the macroscopic structural quality, achieving a more homogeneous and ordered domain orientation, and reduces the lattice parameter ratio (c/a) in the wurtzite crystal structure. The dramatic enhancement of d33 in ScAlN thin films promises extreme frequency scaling opportunities for bulk acoustic wave resonators for beyond-5 G applications.